Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.75.129.1984
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Organic Carbon in South Atlantic Sediments from Deep Sea Drilling Project Leg 75

Abstract: CHN analyses of sediments and rocks sampled during DSDP Leg 75 in the South Atlantic have provided concentrations of organic carbon and atomic C/N ratios of organic matter from two sites. High values of organic carbon were measured in sediments deposited during Neogene and Cretaceous times at Site 530 in the Angola Basin; sediments deposited at other times contain less than 0.5% organic carbon. Development of the Benguela Current and associated upwelling-supported biological productivity is recorded in late Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Considering the good agreement between the CHN (URI) and the RE and LECO determinations, we suspect that the CHN (UM) OC determinations are in error. Earlier comparison of shipboard OC determinations on Leg 75 samples with those done by CHN analyzer at the University of Michigan showed generally good agreement (relative standard deviation ±8.87°7o, Meyers et al, 1984). These comparisons, however, used shipboard bomb CaCO 3 values and hence avoided possible errors from carbonate C measurement by differences that are evident in the present comparison of procedures.…”
Section: Organic Carbonmentioning
confidence: 70%
“…Considering the good agreement between the CHN (URI) and the RE and LECO determinations, we suspect that the CHN (UM) OC determinations are in error. Earlier comparison of shipboard OC determinations on Leg 75 samples with those done by CHN analyzer at the University of Michigan showed generally good agreement (relative standard deviation ±8.87°7o, Meyers et al, 1984). These comparisons, however, used shipboard bomb CaCO 3 values and hence avoided possible errors from carbonate C measurement by differences that are evident in the present comparison of procedures.…”
Section: Organic Carbonmentioning
confidence: 70%
“…Once deposited the decomposition begins, but rapidly strips oxygen from pore waters and from the few centimetres above the bottom, so preservation of organic material is ensured (e.g. Meyers et al 1984). The sedimentary features that the authors observed can be explained by erosion of autochthonous layers, or of the upper parts of turbidites, by later turbidity currents charged with shallow water debris.…”
Section: Discussionmentioning
confidence: 87%
“…[3]); and (3) other organic geochemical and petrographic criteria (e.g. [22,23]). In contrast, the organic matter at Site 603 is mainly of terrigenous origin on the basis of optical [24] and other organic geochemical parameters [25].…”
Section: Source Effectsmentioning
confidence: 99%